A Legal and Socio-Normative Review of Supporting and Hindering Factors in the Free Nutritious Meal (MBG) Policy in Pare District, Kediri - Rindia Fanny Kusumaningtyas; Ellectrananda Anugerah Ash-shidiqqi; Dwiputra Aritenesa; Mutiara Dwi Sari; Nabilla Desyalika Putri (Universitas Negeri Semarang, 2026)
This study discusses the implementation of the Free Nutritious Meal (MBG) Policy in Pare District, Kediri Regency. The focus is on legal and socio-normative aspects of the policy. This study uses a qualitative descriptive approach. The data are taken from statutory regulations, government documents, academic literature, policy reports, and relevant media publications. The findings show that several factors support the implementation of the MBG policy in Pare. These factors include the commitment of local government, support from schools and other local institutions, and public acceptance of the program. In Pare, community values such as mutual assistance and local participation also help the program run at the local level. However, the implementation of the MBG policy still faces several problems. The main problem is regulatory uncertainty. This can be seen from unclear institutional mandates, incomplete operational standards, weak oversight mechanisms, and limited public participation in monitoring and evaluation. Food distribution also remains a challenge, especially when coordination among actors is not yet strong. From a legal perspective, the MBG policy needs clearer implementing regulations and stronger accountability mechanisms. From a socio-normative perspective, the program also needs to consider local conditions, community participation, and equal access to nutritious food. In Pare District, legal certainty and community support must work together so that the policy can be implemented in a fair, accountable, and sustainable manner. This study argues that the effectiveness of the MBG policy does not depend only on food provision. It also depends on regulatory certainty, institutional responsibility, public oversight, and the consistent enforcement of service standards. These elements are important to ensure that the MBG policy supports child nutrition, public welfare, and social justice, aligning with Sustainable Development Goals (SDGs) 12: Responsible Consumption and Production.